2004
DOI: 10.1379/477.1
|View full text |Cite
|
Sign up to set email alerts
|

Serum and lymphocyte levels of heat shock protein 70 in aging: a study in the normal Chinese population

Abstract: Heat shock proteins (Hsps) have been reported to play an important role in both physiological and pathological processes. Hsps also may serve as biomarkers for evaluating disease states and exposure to environmental stresses. Whether Hsp levels in serum and lymphocytes are correlated with age and sex is largely unknown. In this study, we analyzed serum Hsp70 (the most abundant mammalian Hsp) levels by using Western dot blot in 327 healthy male donors aged between 15 and 50 years. We also investigated the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
40
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 44 publications
10
40
0
1
Order By: Relevance
“…In conclusion, this study confirms the results of our pilot study of serum Hsp70 levels in centenarian offspring compared to controls (Terry et al, 2004) and those of Rea at al (Rea et al, 2001) and Jin et al (Jin et al, 2004), showing that serum Hsp70 levels are lower in those individuals that reach an advanced age. In addition, it suggests that low serum Hsp70 levels are associated with longevity independent of other covariates such as age, gender, race, income, alcohol, cardiovascular disease, and a variety of other age-related diseases.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In conclusion, this study confirms the results of our pilot study of serum Hsp70 levels in centenarian offspring compared to controls (Terry et al, 2004) and those of Rea at al (Rea et al, 2001) and Jin et al (Jin et al, 2004), showing that serum Hsp70 levels are lower in those individuals that reach an advanced age. In addition, it suggests that low serum Hsp70 levels are associated with longevity independent of other covariates such as age, gender, race, income, alcohol, cardiovascular disease, and a variety of other age-related diseases.…”
Section: Discussionsupporting
confidence: 90%
“…The Italian centenarian study demonstrated that there were no differences in intracellular Hsp70 among centenarians versus younger controls; however, this study did not examine serum Hsp70. In agreement with our findings, cross-sectional studies carried-out in Ireland (Rea et al, 2001) and in China (Jin et al, 2004) have demonstrated a decline in serum Hsp70 at older ages. It should be noted, however, that none of these studies, including our own, examined the changes in serum Hsp70 in the same individuals over time.…”
Section: Serum Hsp70 Findingssupporting
confidence: 93%
See 1 more Smart Citation
“…However, Hsp70 is down-regulated during the aging process in animal model (Heydari et al, 1994). The down-regulation of Hsp70 in aged human cells has also been reported in some tissues or cell culture systems (Muramatsu et al, 1996;Gutsmann-Conrad et al, 1998;Jin et al, 2004;Jurivich et al, 2005). Therefore, further investigation will be needed to determine if the Hsp70 level decreases in aged human renal medullary cells, and whether or not the level of Hsp70 has any relationship with the decreased renal function.…”
Section: Discussionmentioning
confidence: 96%
“…Their report suggests that cytosolic Hsp70 and DnaJ family proteins or Hsp90 (or both) are induced in CCl 4 -treated rat liver where they may be cytoprotective. A second paper represents a collaboration among investigators at Tongji Medical College and Yanan Hospital in China and at Laval University in Canada (Jin et al 2004). They showed that serum Hsp70 levels increased with age between 15 and 30 years but decreased in individuals between the age of 30 and 50.…”
mentioning
confidence: 99%